QTL analysis for Malt Quality in DH Lines of Barley (Steptoe × Morex) grown in Iran - Mohammad Bahman Sadeghi; Wakil Ahmad Sarhadi; Seyed Ali Peighambari; Mohammad Reza Naghavi; Ahmad Kalbasi Ashtari (Turkish Journal of Agriculture: Food Science and Technology)
In order to study the quantitative variability of malting quality-related traits and to determine the genomic locations which control these traits, an experiment was conducted using one hundred fifty double haploid (DH) lines of barley and their two parents ‛Steptoe’ & ‛Morex’. Protein content (%) was measured using Kjeldahl method, diastatic power calculated with Lintner formula, Malt extract was measured for each by special weight achieved and based on Malt Berix Charts. Transgressive segregation in both directions was observed for all traits. Genetic map is fairly saturated and comprising 327 RFLP markers with a total length of 1226.3cM with an average marker spacing of 3.75cM. Seventeen QTLs by LOD≤2(LRS≤9.21) controlling different studied traits were identified for all studied traits. Total phenotypic variance explained by these QTLs varies from 23.2 to 45.05%. Highest LOD scores were obtained for QTL’s controlling diastatic power (Qdip3Ha) on chromosome 3H, and lowest LOD scores were obtained for QTL’s controlling seed yield per plant (Qsyp1Hb) on chromosome 1H. Therefore gain through marker-assisted selection (MAS) in this population would be limited and some of the “Steptoe× Morex” population was developed with the intention of isolating and advancing barley lines for release to the malting quality.